The Knowledge Based System for Forging Process Design based on Case-Based Reasoning and Finite Element Method - Numthong, C.; Butdee, Suthep (Applied Science and Engineering Progress, 2013)
Forging process design is the crucial task in process planning of forging industry. It is based on the skills and accumulative expertise of the forging experts. Such knowledge of the experts is not easy to elicit directly. However, this knowledge should be managed and used to enhance the efficiency, reduce time and cost of forging process design. The forging process design is to define the process parameters, including initial raw material size, the perform shape and forming steps, the design of a die geometry, the ram velocity, and type of forging (hot or cold forging) and so on. The knowledge of forging process design can be learned and obtained from the previous design cases. This paper presents the integration of case based reasoning and finite element method for supporting forging process design. The previous forging process design cases are stored in case library and it will be retrieved by searching and matching with a new case design. The similar case is reused and revised to solve the new case problem. In addition, a finite element method (FEM) with CAE software is applied to calculate and simulate the forging process in order for making a decision and reducing the forging process and die design trial and error. The new case is tested until the case is successful before retaining in the case library to be reused in the future. The developed system is tested with forging process design of an automotive part.